MANAJAMEN BUDAYA SEKOLAH BERBASIS PEMBIASAAN HARIAN TEMATIK UNTUK INTERNALISASI KEDISIPLINAN DAN CAPAIAN AKADEMIK (STUDI KASUS DI SMK NEGERI 15 GARUT) - Warta, Waska; Maulana, Bagja; Susanti, Hetty; Kosirin, Iis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation and effectiveness of a thematic daily habituation program implemented systematically from Monday to Friday during school entry hours at SMK Negeri 15 Garut. This research was driven by the urgency of vocational education institutions to produce graduates who are not only technically competent but also possess professional work ethics and strong character. Utilizing a qualitative descriptive approach within the framework of Educational Administration, data were gathered through participant observation, documentation of discipline logs, and tracking student academic progress. The data analysis followed an interactive model comprising data reduction, data display, and conclusion drawing. The results demonstrate that structured habituation serves as an effective preventive intervention, producing a